Advances in understanding and modelling the mechanical behaviour of peat - International Workshop on Advances in Understanding and Modelling the Mechanical Behaviour of Peat (1993 : Delft, Netherlands); Haan, Evert Den (Rotterdam : AA Balkema, 1994)
08